Pre- and Post-partum Concentrations of Interleukin 1α, Interleukin 8, and α1-Acid Glycoprotein in Vaginal Fornix and Endometrium of Dairy Cows With Clinical Cervicitis - Vallejo-Timarán, Darío A.; Bazzazan, Ali; Segura, Mariela; Prieto-Cárdenas, Nelson E.; Lefebvre, Rejean C. (Frontiers in Veterinary Science, 2021)
Innate immunity is the principal sensor responsible of the local immune response to control mucosal bacterial contamination of the reproductive tract after parturition, triggering a pro-inflammatory process in the mucosa of the uterus, the vaginal and the cervix. However, knowledge about the inflammation process and outcome of the cervix in dairy cows is scarce even though it plays an important anatomic and functional role between the vagina and the uterus. The objective of the present study was to describe the cellular and humoral local innate immune response during clinical cervicitis (CC) in the uterus and vaginal fornix in pre- and post-partum periods of dairy cows. A retrospective descriptive study was performed involving 26 animals, characterized as clinical cervicitis cows (n=19) and healthy cows (n=7). Blood and mucus of the different compartments of the genital tract were sampled and records of the cows’ genital exam were performed four times: -1w (day -7±2, prepartum), +1w (day +7±4), +3w (day +21±4) and +5w (day +35±4) postpartum. Clinical cervicitis was defined as cows exhibiting a cervix grade–2 and healthy cows were defined as a cow clinically normal with a grade-0 cervix at time +5w. Blood white cell count, vaginal fornix and endometrial neutrophils percentage, and the concentrations of interleukin 1α (IL1), interleukin 8 (IL8), and α1-acid glycoprotein (AGP) in mucus were determined. The results showed that 23% of the cows were categorized as CC at time +5w. Cases of CC with purulent vaginal discharge or subclinical endometritis shown the highest cytokine production. At +3w, IL1, IL8, and AGP concentrations in the uterus and the fornix were significantly higher in CC than healthy cows (CH). In conclusion, the 3-week postpartum is a critical point to evaluate cytokines and acute phase proteins; where IL1 and IL8 variation kept a direct relation with neutrophils numbers and function. The presence of AGP in the endometrium infer a homeostatic proinflammatory protective balance effect, modulating the local uterine innate immune response during peripartum.